Metabolic processes in limfocytes of pathients with varicella zoster infections - Yu. S. Tichonova; G. V. Bulygin; T. Yu. Kuzmina; E. P. Tichonova (Журнал инфектологии, 2014)
Measurement of metabolic processes in lymphocytes in Varicella zoster infection showed highly increased intercellular glycolisys activity with functional cellular overload. Same time, we discovered decreased level of intensivity of first stages of TCC, that rules to lower cycle energetic efficiency and intense metabolitsaminoacides intake for TCC, guiding to high aminoacides transport to lymphocytes. Usage of succinic acid and its salts gives more substrates for TCC, increasing its energetic efficiency and lymphocytes functional activity.